Jumping off the bandwagon : why the most popular charities may not be the best partners in brand/cause collaborations - Coleman, Joshua T.; Sherrell, Dan L. ([London] : SAGE, 2016)
Carter is faced with the challenge of choosing charitable causes for three separate companies to partner with for upcoming cause-related marketing campaigns. He initially thinks that any charitable cause will work due to the generally positive associations of corporate philanthropy, but marketing research informs him that perceptions of brand/cause collaborations may be more complex than has been traditionally assumed. This case encourages students to process the multifaceted nature of charitable causes and the different types of collaborations firms can achieve through brand/cause partnerships.
Description based on online resource; title from home page (viewed on April 21, 2016).
Keywords: elektronické knihy; electronic books; Nonprofit organizations -- Marketing -- Case studies; Social marketing -- Case studies